The Role of Financial Performance in Mediating the Effect of Tax Planning and Corporate Social Responsibility on the Value of Property & Real Estate Companies Listed on the Indonesia Stock Exchange in 2020 - 2023 - Najmatu Rahmah Ali; Dwi Kismayanti Respati (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
The purpose of this study is to find out an overview of how tax planning and corporate social responsibility in Property & Real Estate Sector Companies can affect company value through financial performance as a mediating variable in 2020 - 2023. The data used are financial statements and sustainable reports obtained from the Indonesia Stock Exchange website and the websites of each company with a total sample of 31 companies and 109 total observations. Panel data regression analysis was selected as an analysis technique to test the research data with the help of Eviews 12 software. The results of the tested hypothesis in the form of tax planning affect company value and financial performance, while corporate social responsibility affects company value and financial performance, as well as a significant influence of financial performance on company value. This study also obtained results in the form of a mediating role of financial performance in relation to corporate social responsibility and tax planning affecting company value